2017
DOI: 10.1186/s12913-017-2719-9
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of care as experienced by mental health service users - a qualitative study

Abstract: BackgroundPeople who struggle with mental health problems can provide valuable insight into understanding and improving the coordination of mental health and welfare services. The aims of the study were to explore service users’ experiences and perceptions of continuity of care within and across services relevant to personal recovery, to elicit which dimensions of continuity of care are most essential to service users, and to generate ideas for improving service users’ experiences of continuity of care.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 56 publications
8
87
0
1
Order By: Relevance
“…A study on 323 patients just discharged from psychiatric hospital following compulsory treatment for severe psychosis showed that more frequent changes in the key mental health professional were associated with longer hospital stays (Puntis, Rugkåsa & Burns, 2016). Accordingly, a qualitative study on 10 service users of mental health centres showed that changes in the allocated PMHP were experienced as setbacks in treatment, giving rise to negative feelings (Biringer, Hartveit, Sundfør, Ruud, & Borg, 2017). Even in team-based mental health services, the continuity of the individual relationship with one case manager seemed to play an important role for users' comfort level; users often expressed their preference for working with a particular case manager over others (Stanhope & Matejkowski, 2010).…”
Section: The Change Of the Pmhp: The Importance Of Continuity Of Carementioning
confidence: 99%
“…A study on 323 patients just discharged from psychiatric hospital following compulsory treatment for severe psychosis showed that more frequent changes in the key mental health professional were associated with longer hospital stays (Puntis, Rugkåsa & Burns, 2016). Accordingly, a qualitative study on 10 service users of mental health centres showed that changes in the allocated PMHP were experienced as setbacks in treatment, giving rise to negative feelings (Biringer, Hartveit, Sundfør, Ruud, & Borg, 2017). Even in team-based mental health services, the continuity of the individual relationship with one case manager seemed to play an important role for users' comfort level; users often expressed their preference for working with a particular case manager over others (Stanhope & Matejkowski, 2010).…”
Section: The Change Of the Pmhp: The Importance Of Continuity Of Carementioning
confidence: 99%
“…By offering support before and beyond the inpatient stay, healthcare professionals can emphasize care needs before discharge and address or follow-up with those needs in the community setting. This combination of elements prior to and after discharge fulfils patients' desire for continuity of care (19) and is considered helpful (20) and promising in supporting the effective transition from hospital to community.…”
Section: Introductionmentioning
confidence: 96%
“…It is possible that one-to-one contact with the same HCP enabled patients to feel more comfortable, more trusting of primary care professionals and therefore more likely to engage with the intervention. The value of continuity of care for people with SMI is supported in other work where ongoing personal relationships with family, friends and different healthcare professionals facilitate trust and are central for mental health recovery (24,25). This may explain ndings from the trial that the PRIMROSE intervention was associated with lower costs due to reduced psychiatric admissions (16).…”
Section: Discussionmentioning
confidence: 90%